Changing paradigms of development: an assessment - Farooqui, Jamil (Indian Association of Social Science Institution, 2009)
This paper deals with different approaches to development. It stresses that development is a broad concept which covers all aspects of human life and society. It rejects the interpretation of the concept in terms of economic and political development only. Thus, the most suitable term to highlight the sense and traits of development is ‘social transformation’ or ‘social development’. Sociologists like Comte, Spencer, Tonnies and Durkheim explained changes in the broad sense covering the whole of society. The paper, further, rejects the contemporary view that changes in material conditions initiate changes in the ideological system including standards of morality, values and virtues. All these should be molded according to the traits of material development. The paper highlights the repercussions of this view. If we allow material conditions to change ideological bases, it will destroy the whole fabric of human relations creating conflict, violence, suppression, exploitation and will damage peace,tranquility and human dignity. The paper sets forth the view that changes and development of material conditions should take place according to the ideological bases and cardinal principles of society.